Herd-specific random regression carcass profiles for beef cattle after adjustment for animal genetic merit. (July 2017) - Englishby, Tanya M.; Moore, Kirsty L.; Berry, Donagh P.; Coffey, Mike P.; Banos, Georgios
Abstract: Abattoir data are an important source of information for the genetic evaluation of carcass traits, but also for on-farm management purposes. The present study aimed to quantify the contribution of herd environment to beef carcass characteristics (weight, conformation score and fat score) with particular emphasis on generating finishing herd-specific profiles for these traits across different ages at slaughter. Abattoir records from 46, 115 heifers and 78, 790 steers aged between 360 and 900 days, and from 22, 971 young bulls aged between 360 and 720 days, were analysed. Finishing herd-year and animal genetic (co)variance components for each trait were estimated using random regression models. Across slaughter age and gender, the ratio of finishing herd-year to total phenotypic variance ranged from 0.31 to 0.72 for carcass weight, 0.21 to 0.57 for carcass conformation and 0.11 to 0.44 for carcass fat score. These parameters indicate that the finishing herd environment is an important contributor to carcass trait variability and amenable to improvement with management practices.